Occurrence frequency, molecular evolution and phylogenetic utility of Ulva-specific chloroplast group II intron infA-62 family - Liu, Feng; Jin, Shuangle; Kim, Jang Kyun; Wu, Xiaochan; Wang, Jing (Frontiers in Marine Science, 2025)
Chloroplast intron infA-62 as a degenerated group II intron family was previously observed to exist specifically in infA genes of chloroplast/plastid genomes (plastomes) in the genus Ulva (Ulvophyceae, Chlorophyta). To understand occurrence frequency, molecular evolution and phylogenetic utility of this intron family in Ulva species, in this study, we conducted more sampling tests based on newly designed specific primers, analyzed evolutionary features of its secondary structures, and employed intron infA-62 for phylogenetic analysis of Ulva species. The 100% occurrence frequency of this intron has been observed in Ulva plastomes, supporting its acquisition by the earliest progenitor of Ulva species. The GC content of this intron family is unprecedentedly low (21.0-25.2%) for group II introns. The intron infA-62 family is classified as an atypical form of ORF-less group IIB-like secondary structures. Some new evolutionary features have been revealed in this intron family, including the extremely low GC content in some domains (e.g. domains IB, ICa, ID2, IDa, II and IV), a very short stem in domain I, a drastically changing domain IC2, and a completely degenerated domain IV. Secondary structures of this intron family showed progressive RNA structural deviations and species-specific variations during the Ulva evolution. Nine mutation hotspots have been detected in loop regions of domains IA, IB, IC1, IC2, ICa, IDa, II, IV and VI. The ML phylogenetic tree constructed based on the nucleotide sequences of intron infA-62 showed that Ulva species were classified into two clades representing two Ulva lineages, Ulva I and II, which was consistent with those based on organelle multigene datasets. Our evidences show that intron infA-62 coevolved with the plastomes during the evolution and speciation of Ulva species. The intron infA-62 that combines primary sequence and secondary structure can be used as an efficient phylogenetic marker for identification and classification of Ulva species.